Green synthesis of silver nanoparticles by seaweed endophytic Bacillus siamensis strain CCTB2 and their inhibitory effects against rice blast fungus: Biosynthesis of AgNPs using Bacillus siamensis for protection of rice blast pathogen P. oryzae - Saha, Chaiti; Sultana, Mst Raihana; Khatun, Fahmida; Riya, Efat Tara Yesmean; Kader, Md Abdul; Saikat, Nahid Hasan; Masum, Md Mahidul Islam (Annals of Bangladesh Agriculture, 2026)
Pyricularia oryzae (syn. Magnaporthe oryzae) causes rice blast, which remains a significant threat to global rice production. Chemical fungicides are often used to manage it, but excessive use can have detrimental effects on human health and the environment. Bioinspired nanomaterials offer efficient, cost-effective, and eco-friendly alternatives to traditional methods. This study aimed to synthesize silver nanoparticles (AgNPs) using the seaweed endophytic Bacillus siamensis strain CCTB2 and to evaluate their antifungal effect against the rice blast pathogen P. oryzae. Using 16S rDNA gene sequence analysis, the endophyte bacterial isolate CCTB2, isolated from seaweed, was identified as Bacillus siamensis strain CCTB2. Cell-free supernatants (CFSs) from the seaweed endophytic bacterial strain CCTB2 were used to synthesize the AgNPs, which were then examined using energy-dispersive X-ray spectroscopy (EDX), electron microscopy, Fourier transform infrared spectroscopy (FTIR), and UV-visible spectroscopy. AgNP production was confirmed by the UV-visible spectra, which showed a surface plasmon resonance peak at about 430 nm. The functional groups in the CFSs of isolate CCTB2 that promoted Ag+ reduction, stability, and AgNPs capping were identified by FTIR spectroscopy. AgNPs have a spherical shape with an average particle size of 32.24 nm, according toelectron microscopy. The presence of 2-theta emission peaks in the XRD results indicated that the biosynthesized AgNPs had a crystalline structure. The rice blast pathogen P. oryzae strain MP2 was significantly inhibited by biosynthesized AgNPs at 40 µg/mL, with a mycelial diameter inhibition rate of 96.65%. The mycelial morphology showed swelling and anomalies under microscopy after treatment with AgNPs. To combat rice blast fungus and preserve long-term rice productivity and food security, this study illustrated the development and use of sustainable, environmentally friendly solutions. Ann. Bangladesh Agric. 29(2): 25-44